Significance and Impact of Changing WHO Classification Systems on Glial Tumors with Special Reference to IDH1 Mutation in Resource-Limited Setups - Singh, Divya; Misra, Vatsala; Varma, Kachnar (Asian Pacific Journal of Cancer Biology, 2023)
Objectives: To reclassify glial neoplasms according to the 2021 WHO CNS tumor classification and to study the expression pattern of Isocitrate dehydrogenase 1 (IDH1) mutation by immunohistochemistry(IHC) and to categorize these tumors on the basis of IDH1 mutation. Methods: This retrospective study included patients who were diagnosed as glial tumors on histology (n=60). A detailed clinical history and radiological findings were obtained. Patients above 18 years were taken as adults while age upto 18 years were included in pediatric group. IHC for IDH1 mutation was done using Anti-IDH1 (R132H) antibody. Results: Among all glial tumors, 51.7% (31/60) were assigned IDH1 mutant status and the remaining i.e. 48.3% (29/60) were assigned IDH1 wildtype status. While classifying diffuse gliomas according to age, site and morphology, it was observed that the relative proportion of IDH1 mutant and IDH1 wildtype categories in the adult age group was 56.8% (25/44 cases) and 43.2% (19/44 cases) respectively while in the pediatric age group it was 45.5% (5/11 cases) and 54.5% (6/11 cases) respectively. Among the other glial and glioneuronal tumors majority were IDH1 wildtype (80.0%). Most of the WHO grade 1 tumors were IDH1 wildtype (71.4%, 5/7) whereas Grade 2 and 3 tumors were IDH1 mutant (83.3%, 15/18 and 100.0%, 5/5 respectively). On the other hand in Grade 4 tumors there was a higher proportion of neoplasms exhibiting IDH1 wildtype status (70.0%, 21/30). Conclusion: Identification of IDH status as mutant and wildtype is crucial in glial tumors (especially glioblastoma) because both these groups are clinically, genetically, biologically and prognostically different. IHC provides a standard alternative for molecular studies with high sensitivity and specificity with quick, economical and standard results especially useful in resource-poor countries. Reclassification according to the latest WHO classification appears to confer a overall better prognosis than the previous classifications and this study can also provide a base for future larger research avenues and treatment based on IDH1 mutation.